Felici curiositate. Studies in Latin Literature and Textual Criticism from Antiquity to the Twentieth Century. In Honour of Rita Beyers - Guldentops, Guy; Laes, Christian; Partoens, Gert (Brepols, 2017)
The papers collected in this <span class=